Pengukuran Kinerja Rantai Pasok di Industri Susu: Tinjauan Literatur - Denisa Sri Wahyuni; Laudza Hilmy Adhani Muharam; Sindy Azizah Seviyanti; Wien Kuntari (JURNAL ILMIAH NUSANTARA, 2024)
The cow's milk supply chain management is one of the vital elements in the agricultural industry, playing an important role in connecting milk producers with end consumers. A systematic literature review of articles indexed in scopus, sinta, elsevier, used to analyze and synthesize findings related to the topic. The review methods used were purposive sampling, Supply Chain Operation Reference (SCOR), Analytical Hierarchy Process (AHP). involved direct interviews with milk producers, wholesalers, distributors and retailers in several representative regions. The purpose of this systematic literatur review is to conduct a systematic review of the literature. The data was analyzed using quantitative and qualitative approaches, considering aspects such as performance, risk, collaboration, integration, food safety, environmental sustainability and supply chain management. The results of the critical review show that effective risk management strategies, efficient supply chain management, and collaboration among supply chain stakeholders can improve supply chain efficiency and sustainability. The findings provide a better understanding of the dynamics of the Indonesian cow's milk supply chain and a basis for policy development that can improve the performance and resilience of the domestic agricultural sector.